The control of cracks in pressure vessels exposed to aggressive media - Vitez, Ivan (Materiali in tehnologije, 2000)
In this article the parameters affecting cracking and the crack types that are detected at various stages of a pressure vessel's fabrication and in-service use are described. The inspection for cracking with NDT methods, the repair procedure of pressure vessels (PVs) and the mitigation of cracking are also considered.
Keywords: tlačne posode; varjenje; razpoke; agresivni mediji; neporušne preiskave